AOP Report: Thyroperoxidase Inhibition Leading to Altered Visual Function in Fish Via Altered Retinal Layer Structure. (30th September 2022) - Gölz, Lisa; Baumann, Lisa; Pannetier, Pauline; Braunbeck, Thomas; Knapen, Dries; Vergauwen, Lucia
ABSTRACT: Thyroid hormones (THs) are involved in the regulation of many important physiological and developmental processes, including vertebrate eye development. Thyroid hormone system–disrupting chemicals (THSDCs) may have severe consequences, because proper functioning of the visual system is a key factor for survival in wildlife. However, the sequence of events leading from TH system disruption (THSD) to altered eye development in fish has not yet been fully described. The development of this adverse outcome pathway (AOP) was based on an intensive literature review of studies that focused on THSD and impacts on eye development, mainly in fish. In total, approximately 120 studies (up to the end of 2021) were used in the development of this AOP linking inhibition of the key enzyme for TH synthesis, thyroperoxidase (TPO), to effects on retinal layer structure and visual function in fish (AOP‐Wiki, AOP 363). In a weight‐of‐evidence evaluation, the confidence levels were overall moderate, with ample studies showing the link between reduced TH levels and altered retinal layer structure. However, some uncertainties about the underlying mechanism(s) remain. Although the current weight‐of‐evidence evaluation is based on fish, the AOP is plausibly applicable to other vertebrate classes. Through the re‐use of several building blocks, this AOP is connected to the AOPs leading from TPO and deiodinase inhibition to impaired swim bladder inflation in fish (AOPs 155–159), together forming an AOP network describing THSD in fish. This AOP network addresses the lack of thyroid‐related endpoints in existing fish test guidelines for the evaluation of THSDCs. Environ Toxicol Chem 2022;41:2632–2648. © 2022 SETAC